Screening for specialist palliative care need: Know-how and screening tools Screening auf Bedarf an spezialisierter Palliativversorgung: Know-how und Screeningtools - Müller, Evelyn; Gahr, Susanne; Schnabel, Astrid; Müller, Michael Josef; Sölder, Paul; Tewes, Mitra; Roch, Carmen (Die Onkologie, 2024)
Aim: Specialist palliative care (SPC) should be integrated into the care of patients with advanced cancer with complex symptoms and high burdens. The aim of this publication is to present the screening tools that have the highest relevance for the identification of patients in need of SPC in Germany and that are the most feasible in practice; concrete advice for implementation in practice is also given. Methods: This publication summarizes the results of the subworking group “Screening and timely integration” of the working group Palliativmedizin (CCC Network). These are based on a systematic literature search in Medline and CINAHL that aimed to identify screening tools for SPC need in oncology. Results: From the range of possible screening approaches, the use of patient questionnaires, which are recommended in the German standard operating procedure (SOP) Basic Oncological Screening and are also suitable for SPC screening, is particularly effective. The most relevant options for Germany are the Integrated Palliative Care Outcome Scale (IPOS) and the NCCN Distress Thermometer and Minimal Documentation System (MIDOS2). Initial studies show that these questionnaires have the potential to identify 78–90% of patients in need of SPC using validated cut-off values. Conclusion: Patients with a positive screening result for SPC need are highly burdened. The extent to which the needs can be addressed by the oncological teams or whether SPC should be integrated must then be evaluated. Both patient preferences and local resources of general and specialist palliative care should be taken into account.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Palliative care needs/Patient questionnaires; Palliative care needs/Third party assessment; Patient-reported outcome measures; Screening/Implementation; Tumor diseases/Neoplasms